LITERASI DIGITAL DAN PEMANFAATAN TEKNOLOGI - Karmila Azzahra; Fikri; Resa Siti Patonah; Yulis Damayanti; Munasir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Several factors underlie digital literacy and the use of technology, including globalization and connectivity, education and self-development, as well as challenges related to cyber threats. This study employs a qualitative research method by collecting data through observation and journal article sources. Digital literacy and the use of technology can be defined as an individual’s ability to access and utilize technology effectively, particularly for purposes such as social interaction through digital media. The benefits of Information and Communication Technology(ICT) in developing life skills include financial management skills, communication and collaboration skills, personal skills and self-development, health and well-being, as well as career and employment skills. Practical ways to improve digital literacy in everyday life include regularly learning basic technological skills, critically evaluating information, practicing ethical behavior in digital spaces, and actively engaging and collaborating through technology.